Political will and responsability - Landsbergis , Vytautas (Genocidas ir rezistencija, 2002)
This presentation draws attention to the fact that in Lithuania’s extremely complicated and tragic history of occupations and war crimes in the 20th century, there is a situation where at any given time the focus has been on war crimes committed by one country against Lithuania and its citizens, while war crimes committed by another country have remained in the shadows, which may have influenced the behaviour of the law enforcement agencies and the public’s attitudes towards, and evaluations of, these crimes. The issue of collective and individual responsibility is also discussed
Keywords: war crimes; Soviet Union; Germany; collaborators; responsibility; international law